The Impact of Mobile Applications on the Economic Growth of Indonesian MSMEs - Mufizal, Mufizal (Journal Mobile Technologies (JMS), 2024)
The study investigates how mobile application adoption influences the economic growth of micro, small, and medium enterprises (MSMEs) in Indonesia. Using a mixed-method design that integrates quantitative and qualitative approaches, data were collected from 150 MSME respondents and 20 in-depth interviews across several major provinces. The regression results show that the intensity of mobile application use, digital marketing, and mobile payment integration together explain 67% of business performance variance. MSMEs that actively use mobile tools record an average annual sales growth of 27%, mainly due to increased efficiency, broader market access, and improved financial management. Qualitative findings reinforce these results, showing that digital literacy and adaptive behavior significantly shape the benefits of technological adoption. However, unequal infrastructure and limited digital literacy continue to constrain rural MSMEs. The study concludes that mobile applications serve as key catalysts of innovation and inclusion within Indonesia’s digital economy. Strengthening digital infrastructure, expanding literacy programs, and promoting inclusive financial technology are crucial steps toward sustainable MSME growth.